(untitled) (Journal of Applied Learning and Teaching, 2025)
In the current era of neoliberalism and globalization, the pedagogy of English studies must undergo a radical transformation. This entails integrating cultural components and reconstructing canonical paradigms to address contemporary human and environmental crises within pedagogical frameworks. Greening pedagogy advocates for climate activism, empowering learners to become eco-warriors by fostering critical consciousness about environmental issues facing our planet. In the realm of language education, the National Curriculum Framework (NCF 2005) of India asserts, “Language education is not confined to the language classroom. A science, social science, or mathematics class is ipso facto a language class” (n. p.). According to the NCF, learning a subject goes beyond acquiring knowledge; it involves understanding terminologies, grasping complex concepts, and being able to articulate and critically discuss them. In the educational landscape of India, English is taught in conjunction with other subjects, functioning as a medium of instruction across the curriculum. These intertwining positions underline the fact that all teaching as a form of language education, effectively bridging the gap between ‘English as a subject’ and ‘English as a medium.’ With this perspective in mind, the current study aims to focus on English studies through the lens of Ecopedagogy, utilizing it as a framework and approach to foster eco-awareness. Adopting an analytical approach, this study seeks to apply Ecopedagogical principles to develop a curriculum for English language instruction in higher education institutions.